Recognizing grave socio-economic rights abuses as valid refugee claims under international refugee law - Moustafa, Ramy Mohamed (AUC Knowledge Fountain, 2019)
Article 14 of the Universal Declaration of Human Rights recognizes the right of every person to seek asylum from persecution in other countries. Accordingly, the United Nations adopted the Convention relating to the Status of Refugees in 1951. The Convention, in its first article, sets the definition of the term refugee. It also establishes a criteria that decision makers should follow in order to determine if someone is a refugee. Since the implementation of the Convention, writers and practitioners have regularly been using an approach that maintains a dichotomy between economic migrants and political refugees. This dichotomy is regularly used by decision makers to reject entire classes of applicants on the basis that their claims reflect economic migrant status rather than refugee status. The current situation of global destitution has pushed many people from poor countries to flee to more developed countries where they apply for asylum in order to find protection. These applicants have started to make claims that have begun to challenge the boundaries of the Refugee Convention and question the validity of the traditional dichotomy between economic migrants and political refugees. This paper identifies the conceptual and analytical challenges presented by claims based on economic and social deprivation. It assesses how to overcome these challenges by using a creative interpretation of the Refugee Convention based on recent developments in international human rights law. The central argument of this paper is that in spite of, the traditional dichotomy made between economic migrants and political refugees by legal scholars, the Refugee Convention is capable of accommodating many more claims based on social or economic deprivation. To prove this argument, the paper analyzes each element of the refugee definition and shows how socio-economic-based claims can fulfill the requirements of a refugee claim.